2011
DOI: 10.1597/09-161
|View full text |Cite
|
Sign up to set email alerts
|

Speech and Magnetic Resonance Imaging Results following Autologous Fat Transplantation to the Velopharynx in Patients with Velopharyngeal Insufficiency

Abstract: Autologous fat transplantation to the velopharynx resulted in a significant reduction of the velopharyngeal distance and the velopharyngeal gap area during phonation, as measured by MRI. This was in accordance with a significant improvement in nasal turbulence. However, hypernasality and audible nasal emission did not change significantly and could not be correlated to the MRI findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 32 publications
0
19
0
1
Order By: Relevance
“…Recently, only one report discussed augmentation that was limited to the soft palate [23]. Furthermore, many reports on velopharyngeal augmentation have found that this treatment did not improve hypernasality in some VPI patients [13,15,18,19,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, only one report discussed augmentation that was limited to the soft palate [23]. Furthermore, many reports on velopharyngeal augmentation have found that this treatment did not improve hypernasality in some VPI patients [13,15,18,19,21,23].…”
Section: Discussionmentioning
confidence: 99%
“…Las insuficiencias velo faríngeas se han definido como la incapacidad del velo palatino en la obturación del esfínter velo faríngeo (Filip et al, 2011;Ministerio de Salud;Ysunza et al, 2002) permitiendo el escape del aire hacia la cavidad nasal durante la emisión de los fonemas vocálicos y consonánticos, excepto para m, n y ñ que son por naturaleza nasales (Cortés Araya et al). Se ha propuesto como medida terapéutica para este trastorno la realización de una cirugía secundaria de velo palatino en conjunto con tratamiento fonoaudiológico.…”
Section: Discussionunclassified
“…Several reports have described another method for treating VPI [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. Velopharyngeal structure augmentation is an alternative to pharyngeal flap surgery that utilizes an injectable material implanted into the tissue around the velopharynx.…”
Section: Introductionmentioning
confidence: 99%
“…There have been no reports about the optimal materials for implantation or injection, however. There are various artificial and biological materials that may be used in the velopharyngeal structure, including silicone, Teflon, porous polyethylene, Gore-Tex 1 , calcium hydroxyapatite, auricular or costal cartilage, and autologous fat [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, when we augment the soft palate, the material needs to be injectable, because it cannot be implanted into the nasal side of the soft palate without damaging the levator veli palatini.…”
Section: Introductionmentioning
confidence: 99%